Analisis Kualitas Lingkungan Belajar Berdasarkan Persepsi Siswa Pada Mata Pelajaran Biologi - Veni Wulandari; Indri Astuti; Afandi (Jurnal Biotek, 2022)
The success of students in the aspects of knowledge and skills is indispensable in this century. The quality of the learning environment is one of the factors that affects how well students learn biology. This study aimed to analyze the quality of the learning environment in biology at SMA Negeri 1 Kayan Hilir based on students' perceptions. The research was a descriptive quantitative research method. The instrument in this research was a questionnaire with as many as 56 questions consisting of 7 indicators, namely: student cohesiveness, teacher support, involvement, inquiry/investigation of learning, task orientation, cooperation, and equity/rights of each student (validity >0.8 (high category, V = 1) and reliability = 0.914). The sample in this study was 43 students at SMA Negeri 1 Kayan Hilir. Data collection was done through a questionnaire survey, which was then analyzed using a quantitative descriptive method, which was then converted into a Likert scale. Through this study, the average quality of the learning environment in SMA Negeri 1 Kayan Hilir was 84.69. These results were obtained from the average value of each indicator. This study concludes that students' perceptions state that the quality of the learning environment in biology at SMA Negeri 1 Kayan Hilir is very good (mean = 84.69).